Slave : the hidden truth about your identity in Christ - MacArthur, John 1939-; MacArthur, John (Nashville [Tenn.] : Thomas Nelson, 2010)
John MacArthur uses deep Bible teaching and historical evaluation to expertly uncover the one forgotten word that restores the Bible's definition of true Christian freedom. What does it mean to be a Christian the way Jesus defined it? MacArthur says it all boils down to one word: Slave. "We have been bought with a price. We belong to Christ. We are His own possession." --from publisher description
One hidden word -- Ancient history, timeless truth -- The good and faithful slave -- The Lord and master (pt. 1) -- The Lord and master (pt. 2) -- Our Lord and our God -- The slave market of sin -- Bound, blind, and dead -- Saved from sin, slaved by grace -- From slaves to sons (pt. 1) -- From slaves to sons (pt. 2) -- Ready to meet the master -- The riches of the paradox -- Appendix. Voices from church history.
Includes bibliographical references.
Keywords: Identification (Religion); Christian life